2010
DOI: 10.3340/jkns.2010.48.6.506
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cognitive Level Explanation Model in Brain Injury : Comparisons between Disability and Non-Disability Evaluation Groups

Abstract: Objective :We investigated whether Disability Evaluation (DE) situations influence patients' neuropsychological test performances and psychopathological characteristics and which variable play a role to establish an explanation model using statistical analysis. Methods : Patients were 536 (56.6%) brain-injured persons who met inclusion and exclusion criteria, classified into the DE group (DE; n = 300, 56.0%) and the non-DE group (NDE; n = 236, 44.0%) according to the neuropsychological testing's purpose. Next,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition, the PC-G showed more severe subjective symptoms on Som, OC, Host, and Phob than the CC-G. This means that participants with malingering tendencies prefer to fake bad symptoms about these aspects, which may be unconscious (or passive) exaggeration due to a defense mechanism (for example, the conversation of psychological confliction into somatic symptoms, that is, Som) or simply because of how easily the symptom can be simulated ( Shin et al, 2010 ; Sullivan and King, 2010 ). These results were consistent with the previous findings that psychopathologies such as posttraumatic stress disorder, somatic complaints, depression, psychoticism, and phobic anxiety were more susceptible to malingering ( Sullivan and King, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the PC-G showed more severe subjective symptoms on Som, OC, Host, and Phob than the CC-G. This means that participants with malingering tendencies prefer to fake bad symptoms about these aspects, which may be unconscious (or passive) exaggeration due to a defense mechanism (for example, the conversation of psychological confliction into somatic symptoms, that is, Som) or simply because of how easily the symptom can be simulated ( Shin et al, 2010 ; Sullivan and King, 2010 ). These results were consistent with the previous findings that psychopathologies such as posttraumatic stress disorder, somatic complaints, depression, psychoticism, and phobic anxiety were more susceptible to malingering ( Sullivan and King, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Objectively speaking, this contradiction was not incomprehensible. In addition to the poor effort due to interests pursued ( Shin et al, 2010 ; Silver, 2012 ), the bad influences on different aspects of cognitive functions, including IQ (executive functions, information processing speed, attention and visuomotor functioning, memory, naming, and verbal knowledge), are related to the diverse localization of brain lesions ( Miotto et al, 2010 ; Königs et al, 2016 ). As the cases were collected, the injured areas of the brain varied among the included participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult patients that had undergone disability evaluation after TBI showed differences in neurocognitive outcomes according to the cause of visit, and showed lower performance than the treatment group (patients who were scheduled to undergo disability evaluation after recovering from TBI). This suggested that disability evaluation process has an effect on the test-taking attitude or will affect the attitude of the clinician administering the test or the patient actually taking the test intentionally or unintentionally 20) . Therefore, clinicians should not assume that old aged patients with TBI are "faking" their symptoms or injuries as adult patients with TBI, but assume that they could faking their performance in a test set available visual feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the patients with mild TBI in this study had external incentives to malinger and displayed definite or probable malingered neurocognitive dysfunction 23) . 40.3% of DE patients with mild and moderate brain injuries display typical or passive malingering patterns and behaviors, sometimes involving denial of symptoms and resistance to treatment 22) .…”
Section: Discussionmentioning
confidence: 99%